Home-School Collaboration: Maximizing Resources and Efforts to Support Students’ Independent Learning - Rosales, Rolly A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Home-school collaboration is a valuable strategy for fostering independent learning. Hence, it must be explored in the context of the new normal where the printed modular learning modality is the widely chosen learning delivery among public schools across the country. This study explored how home-school collaboration cultivates and fosters students’ independent learning in the new normal across the districts of Bilar, Batuan, Carmen, and Sierra Bullones, Division of Bohol, as of the school year 2021 – 2022, with the end goal of proposing a home-school program initiative. A descriptive qualitative research design was employed through an open-ended survey method and semi-structured interview to gather the required data. Thematic Analysis was used in making sense of the data. The results revealed that home school collaboration involves providing the necessary learning resources and exerting efforts to support independent learning. Learning resources were key instructional or supplemental in nature. Efforts exerted by the people behind this collaboration include parent-teacher partnerships, the provision of learning resources, and remedial instruction. The themes that emerged from the discussion showed that the collaborative efforts between teachers and parents fostered independent learning, which has a facilitative effect on their cognitive, affective, and psychomotor domains. Thus, the learners evidently showed clear manifestations of independent learning, such as an optimistic attitude towards answering modules, eagerness to learn, enhanced reading performance, and a clear indication of integrity in answering their self-learning modules. However, some identified factors could hinder school-school collaborative efforts based on the participants' narratives, such as family, school-related, learning resources, and personal factors. In capsule, home-school collaboration is a valuable strategy for fostering independent learning through its facilitative effect on the learner's mind, emotion, and behaviors.